Missed Opportunity for Neonates to Live: A Cross-Sectional study on Utilization of Peri-Natal Death Audits to address the Causes of Peri-Natal Mortality in District Hospitals of East–Central Uganda. - Knox Waako, Christopher; Nanyingi, Miisa; Katongole, Simon Peter; Atuhairwe, Christine; Konso, Jennipher Mariam; Maniple, Everd (Student’s Journal of Health Research Africa, 2022)
Aim: To assess the utilization of PDAs in addressing the avoidable causes of perinatal mortality in the eastern region of Uganda. Methodology: A cross-section design using a mixed method was conducted between 2014-2015 at Iganga, Bugiri, and Kamuli general hospitals in the East-Central region of Uganda. The interviews involved 115 health workers who included Doctors, Nurses/Midwives, Clinical officers, and Laboratory and Theatre staff. These were drawn from four departments including the Maternity ward, Outpatient department, Theatre, and pediatric ward. Hospital top and departmental managers formed the key informants for this study. Annual reports for the period 2009/10-2012/13 were reviewed. In addition, monthly reports for the calendar year 2013 together with patients’ clinical case notes and patients’ registers were also reviewed to determine the magnitude and causes of perinatal mortality. Factors contributing to perinatal death were assessed and categorized into fetal, maternal, and health facility factors. Results: Results revealed a high and rising perinatal mortality rate of 70/1,000 live births and a decreasing maternal mortality ratio of 363/100,000 live births. Most perinatal deaths were fresh stillbirths 48/88 which occurred during the intrapartum period and the majority of early neonatal death was due to birth asphyxia. None of the health facilities was conducting perinatal death audits and the quality of data used for perinatal death audits was inadequate and was scored poorly. Challenges hindering utilization of perinatal death audits included lack of staff sensitization and training, work overload, lack of motivation, fear of blame and litigation, political interference, and lack of support from the community. Conclusion: There was a high prevalence of perinatal deaths in east-central Uganda yet none of the hospitals was conducting perinatal death reviews. Recommendations: Health workers should be trained on perinatal death audit tools and guidelines. Records departments to revitalize with tools and personnel for effective data management.